2015
DOI: 10.1037/abn0000067
|View full text |Cite
|
Sign up to set email alerts
|

Examining associations between psychosis risk, social anhedonia, and performance of striatum-related behavioral tasks.

Abstract: Both psychosis and anhedonia have been associated to some extent with striatal functioning. The current study examined whether either psychosis risk or social anhedonia was associated with performance on three tasks related to striatal functioning. Psychosis risk participants had extremely elevated Perceptual Aberration/Magical Ideation (PerMag) scores (n=69), with 43% of psychosis risk participants also having semi-structured interview-assessed psychotic-like experiences which further heightens their risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 97 publications
(171 reference statements)
4
14
2
Order By: Relevance
“…Similarly, other behavioral research also has found that increased dopamine in the striatum is related to increased sensitivity to learning from rewards (Frank et al, 2004). Hence, the current evidence of PE being associated with greater sensitivity to learning from unexpected reward than from unexpected punishment is consistent with increased dopamine in the striatum in people with psychosis risk (Karcher et al, 2015b).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Similarly, other behavioral research also has found that increased dopamine in the striatum is related to increased sensitivity to learning from rewards (Frank et al, 2004). Hence, the current evidence of PE being associated with greater sensitivity to learning from unexpected reward than from unexpected punishment is consistent with increased dopamine in the striatum in people with psychosis risk (Karcher et al, 2015b).…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to the PE group, the social anhedonia group did not differ from the control group in their behavioral performance or in their FRN for unexpected trials on the RLT, suggesting that some aspects of reward and punishment-based learning may to some extent be intact in people with extremely elevated social anhedonia who are at increased risk for schizophrenia-spectrum disorders (Karcher et al, 2015b;Padrao et al, 2013). Future research should continue to examine whether some particular aspect of reward and punishment-based learning, perhaps reward anticipation (Dowd and Barch, 2012;Juckel et al, 2006), is associated with anhedonia in at risk groups.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The current ERP study participants were Introductory to Psychology students who participated for course credit after taking part in a separate behavioral testing session (Karcher, Martin, & Kerns, 2015). As can be seen in Table 1, there were no significant between group differences on any demographic variable we assessed.…”
Section: Methodsmentioning
confidence: 99%